2006
DOI: 10.1055/s-2006-951300
|View full text |Cite
|
Sign up to set email alerts
|

Association of Necrotizing Enterocolitis with Elective Packed Red Blood Cell Transfusions in Stable, Growing, Premature Neonates

Abstract: The purpose of this study was to determine an association between packed red blood cell (PRBC) transfusions for anemia and necrotizing enterocolitis (NEC) in a subset of stable, growing, premature neonates. As part of a survey of current clinical practices over a 17-month period from June 1999 to October 2000, a chart review was performed to determine the relationship between elective PRBC transfusions and the occurrence of NEC. Demographic data were tabulated and compared between the NEC patients with a prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(121 citation statements)
references
References 28 publications
9
106
5
1
Order By: Relevance
“…12 The association between NEC and red blood cell (RBC) transfusion has been a subject of recent debate. [13][14][15][16][17] On the basis of this presumptive association between RBC transfusion and NEC, some NICUs have set their policy to avoid feeding during transfusion. 18 A recent study demonstrated that transfusion negatively affects the post-prandial increase in mesenteric blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…12 The association between NEC and red blood cell (RBC) transfusion has been a subject of recent debate. [13][14][15][16][17] On the basis of this presumptive association between RBC transfusion and NEC, some NICUs have set their policy to avoid feeding during transfusion. 18 A recent study demonstrated that transfusion negatively affects the post-prandial increase in mesenteric blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have noted a similar 27,28 However, the nature of this association remains to be fully explored; it is unclear that this is truly a causative relationship. It is possible that patients who are beginning to manifest systemic signs of illness are more likely to have laboratory tests performed and perhaps a lowered transfusion threshold is applied.…”
Section: Discussionmentioning
confidence: 92%
“…[27][28][29] To this end, the conservative feeding transfusion policy of holding feeds and/or not changing volume or fortification on the same day as a transfusion was felt to be of low risk and potentially high benefit to the reduction of the incidence of NEC. Despite the overall decrease use of indomethacin therapy for hemodynamically significant patent ductus arteriosus, we instituted a conservative feeding guideline to ensure use of a standardized feeding regimen in our neonatal network.…”
Section: Figurementioning
confidence: 99%